Right ventricular energy failure predicts mortality in patients with pulmonary hypertension - KOCAKAYA, DERYA (My University, 2023)
Right ventricular (RV) failure has a significant adverse impact on pulmonary hypertension (PH) prognosis. None of the currently used parameters directly assess whether RV fails to provide enough energy output to propel the blood through diseased pulmonary vascular system. Furthermore, most of the current parameters are affected by the volume status of the patient. We aimed to explore whether RV energy failure has a predictive power for mortality on top of the established prognostic risk parameters in patients with PH. We screened 723 cases from our database. A total of 3 sets of binary regression analyses were executed to determine the hazard ratios (HRs) of RV energy failure for 5-year mortality in clinical, echocardiographic, and hemodynamic context, using adjustment variables chosen according to previous studies. The final study population encompassed 549 cases. A total of 77 patients died during the 5-year follow-up (14%). RV energy failure was observed in 146 of 549 patients (26.6%). In the univariate model, RV energy failure strongly associated with increased long-term mortality (HR 4.25, 95% confidence interval [CI] 2.58 to 7.00, p <0.001). It also emerged as a significant predictor of long-term mortality in clinical and hemodynamic multivariate models (HR 2.59, 95% CI 1.43 to 4.67, p = 0.002 and HR 2.05, 95% CI 1.15 to 3.63, p = 0.015, respectively). In conclusion, our study indicates that the presence of RV energy failure independently predicts long-term mortality in PH. © 2023 Elsevier Inc. All rights reserved. (Am J Cardiol 2023;193:19−27)
Keywords: 6MWT; six-minute walk test; NT pro-BNP; N-terminal pro-brain natriuretic peptide; PCWP; pulmonary capillary wedge pressure; PH; pulmonary hypertension; PVR; pulmonary vascular resistance; RA; right atrium; RHC; right heart catheterization; RV; right ventricle; sPAP; systolic pulmonary artery pressure ratio; TAPSE; tricuspid annular plane systolic excursion; WHO; World Heart Organization